2011
DOI: 10.1007/s11010-011-0733-5
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian cell entry gene family of Mycobacterium tuberculosis

Abstract: Knowledge of virulence factors is important to understand the microbial pathogenesis and find better antibiotics. Mammalian cell entry (mce) is a crucial protein family for the virulence of Mycobacterium tuberculosis (M. tuberculosis). This review summarized the advances on mce genes. The genomic organization, characteristics of mce genes, phylogeny of this family, and their roles in M. tuberculosis virulence are emphasized in this review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
90
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(94 citation statements)
references
References 47 publications
3
90
0
1
Order By: Relevance
“…Proteins-Mammalian cell entry (Mce) family proteins are crucial for the virulence of mycobacteria and represent components of transport systems that interact with host cells (68). Structural analysis has indicated that some Mce proteins are similar to colicins or ß-barrel porins, which form channels through lipid bilayers (69).…”
Section: Mammalian Cell Entry Familymentioning
confidence: 99%
See 1 more Smart Citation
“…Proteins-Mammalian cell entry (Mce) family proteins are crucial for the virulence of mycobacteria and represent components of transport systems that interact with host cells (68). Structural analysis has indicated that some Mce proteins are similar to colicins or ß-barrel porins, which form channels through lipid bilayers (69).…”
Section: Mammalian Cell Entry Familymentioning
confidence: 99%
“…Most interestingly, mce family genes are absent from the human genome. Therefore, Mce proteins might represent ideal candidate drug targets for better TB therapeutics (68).…”
Section: Mammalian Cell Entry Familymentioning
confidence: 99%
“…MMP9 has enzymatic activity required for the development of the hallmark inflammatory granulomatous tissue reaction in the host (106). Next, intracellular invasion is mediated by phagocytosis or macropinocytosis in an Mce protein family-dependent manner, involving direct molecular interaction with the host, although the targeted host proteins are still unknown (107,108).…”
Section: Function and Interaction Of Individual Proteins And Complexesmentioning
confidence: 99%
“…Interestingly, unlike rapidly growing mycobacteria, our analysis of the M. phlei genome showed that this genome encodes a putative mammalian cell entry (MCE) operon, which was previously shown to be conserved only among slow-growing mycobacteria. This virulence factor operon in nonpathogenic Escherichia coli confers the ability to invade and survive inside host cells, such as macrophages and HeLa cells (3,13). Further genomic and functional analyses are needed to investigate this observation.…”
mentioning
confidence: 99%